TECHNOLOGY ACCEPTANCE AND CUSTOMER SATISFACTION IN DIGITAL ISLAMIC FINANCIAL SERVICES - Syuhada' Syuhada' (Study Program of Sharia Business Management , Faculty of Islamic Economics and Business, 2026)
The rapid growth of digital technology has transformed the Islamic financial industry by enabling the development of innovative, accessible, and Sharia-compliant financial services. This study aims to explore the relationship between technology acceptance and customer satisfaction in digital Islamic financial services. Employing a qualitative research approach, the study investigates how perceived usefulness and perceived ease of use influence customers’ experiences and satisfaction when utilizing digital Islamic financial platforms. Data were collected through in-depth interviews, document analysis, and relevant literature reviews, and subsequently analyzed using thematic analysis. The findings reveal that customers generally perceive digital Islamic financial services as beneficial in enhancing transaction efficiency, accessibility, convenience, and financial management. Furthermore, ease of use, system reliability, security, and privacy protection contribute significantly to positive customer experiences. The study also finds that Sharia compliance, ethical values, and customer trust play critical roles in strengthening the relationship between technology acceptance and customer satisfaction. These findings support the Technology Acceptance Model (TAM) while extending its applicability to the context of digital Islamic financial services. The study contributes to the growing literature on Islamic digital finance by providing a comprehensive understanding of how technological and religious factors jointly influence customer satisfaction. Practically, the findings offer valuable insights for Islamic financial institutions seeking to improve digital service quality, enhance customer trust, and strengthen long-term customer relationships in an increasingly competitive digital environment.